The Effect of Glucagon-Like Peptide 1 Receptor Agonists on Weight Loss in Type 2 Diabetes: A Systematic Review and Mixed Treatment Comparison Meta-Analysis - Potts, Jessica E.; Gray, Laura J.; Brady, Emer M.; Khunti, Kamlesh; Davies, Melanie J.; Bodicoat, Danielle H. (PLOS ONE, 2015)
Aims To determine the effects of glucagon-like peptide-1 receptor agonists compared with placebo and other anti-diabetic agents on weight loss in overweight or obese patients with type 2 diabetes mellitus. Methods Electronic searches were conducted for randomised controlled trials that compared a glucagon-like peptide-1 receptor agonist therapy at a clinically relevant dose with a comparator treatment (other type 2 diabetes treatment or placebo) in adults with type 2 diabetes and a mean body mass index ≥ 25kg/m2. Pair-wise meta-analyses and mixed treatment comparisons were conducted to examine the difference in weight change at six months between the glucagon-like peptide-1 receptor agonists and each comparator. Results In the mixed treatment comparison (27 trials), the glucagon-like peptide-1 receptor agonists were the most successful in terms of weight loss; exenatide 2mg/week: -1.62kg (95% CrI: -2.95kg, -0.30kg), exenatide 20μg: -1.37kg (95% CI: -222kg, -0.52kg), liraglutide 1.2mg: -1.01kg (95%CrI: -2.41kg, 0.38kg) and liraglutide 1.8mg: -1.51 kg (95% CI: -2.67kg, -0.37kg) compared with placebo. There were no differences between the GLP-1 receptor agonists in terms of weight loss. Conclusions This review provides evidence that glucagon-like peptide-1 receptor agonist therapies are associated with weight loss in overweight or obese patients with type 2 diabetes with no difference in weight loss seen between the different types of GLP-1 receptor agonists assessed.